Triphthong Pronunciation Errors: An Analysis of English Education Students - Maemuna Muhayyang; Fitri Radhiyani; Andi Asrifan (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
A crucial component of learning English is pronunciation, which is necessary for efficient and transparent communication. Students frequently struggle, nevertheless, especially when it comes to complicated vowel sounds like triphthongs (/aʊə/, /aɪə/, /eɪə/, /oʊə/, /ɔɪə/). This study is to analyze the types and causes of triphthong pronunciation errors among English education students at Universitas Negeri Makassar. By identifying the common mistakes, it is able to understand the influence of first language interference, motivation, and learning exposure on pronunciation accuracy to provide insights into effective teaching strategies to improve students’ phonetic competence, enhance pronunciation instruction, and support clearer communication in English as a result. Ten students who have trouble pronouncing triphthongs are used as the study's sample, and it uses a qualitative approach using a case study design. Semi-structured interviews were used to gather the data, and Miles and Huberman's narrative data analysis (1994), which includes data gathering, data reduction, data presentation, and conclusion drawing, was used to evaluate the data. According to the findings, (1) the most frequent mistakes were substitution, omission, and distortion; and (2) the interference of students' native tongues and the appearance of their learning attitude, demotivation, and age as contributing factors to having a good pronunciation for the triphthong sounds. This study advances our knowledge of pronunciation difficulties and offers suggestions for enhancing pronunciation instruction in English classes.